Riemann boundary-value problem on an open rectifiable jordan curve. I - Kud'yavina, Yu. V.; Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The Riemann boundary-value problem is solved for the classes of open rectifiable Jordan curves extended as compared with previous results and functions defined on these curves.